2017
DOI: 10.18520/cs/v112/i06/1272-1276
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Particulate Pollution on Photosynthesis, Transpiration and Plant Water Potential of Teak (<i>Tectona grandis</i> L.)

Abstract: The study on teak Tectona grandis L. under particulate pollution stress caused by deposition of cement dust revealed that various physiological functions were hampered due to these pollutants. The dust accumulation was highest during summer (0.299 mg/ sq. cm) in the polluted plot in comparison to control plot (0.037 mg/sq. cm). The effects of particulate pollution on T. grandis also varied with season, with a general trend of particulate pollutants having maximum effect on vegetation during summer and least du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The small sized matters were tightly adhered to leaf surface, but larger substances were washed away by rain. Anoob, Santhoshkumar & Roby (2017) showed that chlorophyll pigment amount decreased as pollution was heavier and dirt layer was highest in dry summer by the reason of long exposure time and not enough rainfall to wash the dust off the leaves. Prajapati and Tripathi (2008) showed that level of chlorophyll reduced with the increase of dust deposition and the maximum dust deposition was observed in winter by summer.…”
Section: Discussionmentioning
confidence: 99%
“…The small sized matters were tightly adhered to leaf surface, but larger substances were washed away by rain. Anoob, Santhoshkumar & Roby (2017) showed that chlorophyll pigment amount decreased as pollution was heavier and dirt layer was highest in dry summer by the reason of long exposure time and not enough rainfall to wash the dust off the leaves. Prajapati and Tripathi (2008) showed that level of chlorophyll reduced with the increase of dust deposition and the maximum dust deposition was observed in winter by summer.…”
Section: Discussionmentioning
confidence: 99%